Photonic Efficiency of the Photodegradation of Paracetamol in Water by the Photo-Fenton Process - Yamal Turbay, E. (2015)
An experimental study of the homogeneous Fenton and photo-Fenton degradation of 4-amidophenol (paracetamol, PCT) is presented. For all the operation conditions evaluated, PCT degradation is efficiently attained by both Fenton and photo-Fenton processes. Also, photonic efficiencies of PCT degradation and mineralization are determined under different experimental conditions, characterizing the influence of hydrogen peroxide (H2O2) and Fe(II) on both contaminant degradation and sample mineralization. The maximum photonic degradation efficiencies for 5 and 10 mg L−1 Fe(II) were 3.9 (H2O2=189 mg L−1) and 5 (H2O2=378 mg L−1), respectively. For higher concentrations of oxidant, H2O2 acts as a "scavenger" radical, competing in pollutant degradation and reducing the reaction rate. Moreover, in order to quantify the consumption of the oxidizing agent, the specific consumption of the hydrogen peroxide was also evaluated. For all operating conditions of both hydrogen peroxide and Fe(II) concentration, the consumption values obtained for Fenton process were always higher than the corresponding values observed for photo-Fenton. This implies a less efficient use of the oxidizing agent for dark conditions.